2008
DOI: 10.1016/s1808-8694(15)30750-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of myelinic fibers in human laryngeal nerves according to age

Abstract: The total number of myelinic fibers in laryngeal nerves is higher for the group aged below 60 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
(66 reference statements)
6
6
0
Order By: Relevance
“…Bodies with a history of diabetes showed lower numbers of thick myelinated axons. This suggests that diabetes could lower the number of myelinated axons in addition to chronic alcoholism and aging, in line with the literature (Guo et al, ; Mortelliti et al, ; Tiago et al, ). However, no reduction in axon number was noted in body #8 with a history of alcoholism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Bodies with a history of diabetes showed lower numbers of thick myelinated axons. This suggests that diabetes could lower the number of myelinated axons in addition to chronic alcoholism and aging, in line with the literature (Guo et al, ; Mortelliti et al, ; Tiago et al, ). However, no reduction in axon number was noted in body #8 with a history of alcoholism.…”
Section: Discussionsupporting
confidence: 89%
“…Numbers of A beta axons in TVN fit nicely to figures obtained by subtracting the number of A alpha motor axons in the RLN from the total thick myelinated axon count in the CVN. Numbers of presumed A alpha axons in the RLN of our sample corresponded well to data from the literature (Tiago et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…However, there is no evidence of a difference between the number of unmyelinated fibres in the two nerves. We accept that this finding represents at most a notable point of interest; however, it does correspond with findings from Tiago and colleagues' studies, 11,15 which clearly demonstrated a significant decrease in the total number of myelin fibres in elderly patients. 7 Alternatively, in the words of Dilworth, 'these nerves were a plexus [, with the] vagus represented by a continuous nerve joining the internal and recurrent nerves and […] separation from this strand form[ing] the individual nerves of the larynx'.…”
Section: Discussionsupporting
confidence: 89%
“…11,15 This group described the superior laryngeal nerve as having over double the number of myelinated fibres of the recurrent laryngeal nerve. 11,15 This group described the superior laryngeal nerve as having over double the number of myelinated fibres of the recurrent laryngeal nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation